Virtual literacies : interactive spaces for children and young people - Merchant, Guy. (Routledge research in education ;, 2013)
"The growth of interest in virtual worlds and other online spaces for children and young people raises important issues for literacy educators and researchers. This book is a timely and much-needed collection of current research in the area. It provides a synthesis of knowledge and understanding and will be a key resource for scholars, students and teachers, particularly those interested in digital literacies. The work presents a coherent vision of current knowledge, and some of the most engaging, empirical research being undertaken on virtual worlds and online spaces in and beyond educational institutions. It contains international studies from the UK, North America and Australasia. This is an important time for those researching virtual worlds, videogaming and Web 2.0 technologies, since there is growing professional interest in their significance in the education and development of children and young people. Whether these technologies are solely associated with informal learning or whether they should be incorporated into classroom contexts is hotly debated. This book provides a principled evaluation and appreciation of the learning, teaching and instruction that can occur in digital environments, showing children, young people and those who work with them as active agents with possibilities to navigate new paths"--